Studies in law, politics, and society. Vol. 66 - Sarat, Austin (Bingley, U.K. : Emerald, 2015)
"The articles in this volume of Studies in law, politics, and society cover an exciting and diverse range of topics relating to laws relationship with and impact on society. Two articles cover immigration, but from very different perspectives. One examines the legal-cultural attitude of immigrants from the former Soviet Union to Israel while the other investigates US Immigration Policy and the notion of child saving. Other articles cover the institutional dynamics of same-sex marriage debates in America; the anti-strip mining movement in central Appalachia; an analysis of the death penalty in Maricopa County, Arizona, one of the most active death penalty locales in the contemporary U.S; and affirmative defenses at the International Criminal Court."
Rights discourse and the mobilization of bias : exploring the institutional dynamics of the same-sex marriage debates in America / Joseph Mello -- Unearthing a network of resistance : law and the anti-strip mining movement in central Appalachia / Robert Todd Perdue, Christopher McCarty -- Racist localisms and the enduring cultural life of America's death penalty : lessons from Maricopa County, Arizona / Benjamin Fleury-Steiner, Paul Kaplan, Jamie Longazel -- Towards justice : neuroscience and affirmative defenses at the ICC / Adam B. Shniderman, Charles A. Smith -- While in Rome, do as Romans do? Persistence of legal culture : the case of immigrants from the former Soviet Union to Israel / Julia Shamir -- US immigration policy and the 21st century conundrum of child saving : a human rights, law and social science, political economic and philosophical inquiry / S. Lorén Trull, Bruce A. Arrigo.
Print version record
Keywords: Law -- General; Law & society; Human rights & civil liberties law; Sociological jurisprudence; Law -- Political aspects